The effect of inspiratory muscle training on clinical outcomes and health-related quality of life in children with neuromuscular disease and respiratory muscle weakness. - Human, Anri (Division of Physiotherapy, 2022)
Background: Progressive respiratory muscle weakness and ineffective cough contributes to pulmonary morbidity and mortality in children with neuromuscular disease. Inspiratory muscle training aims to preserve or improve respiratory muscle strength, reduce respiratory complications and improve health-related quality of life. Objectives: To describe South African physiotherapists' knowledge and respiratory management strategies and determine the safety, viability, acceptability and efficacy of inspiratory muscle training for children 5-18 years with neuromuscular disease. Methods: Four studies were conducted: i) a quantitative descriptive survey; ii) a systematic review using Cochrane methodology; iii) a prospective, pre-experimental observational study and iv) a prospective, cross-over randomised controlled trial using a standardised 12-week inspiratory muscle training intervention. Results: i) South African physiotherapists (n=64) reported being aware of international clinical practice recommendations, however they favoured manual airway clearance techniques. The use of inspiratory muscle training in chronic management was well supported by South African physiotherapists. ii) Results of the systematic review (seven included studies; n=168) suggested that inspiratory muscle training may be effective in improving inspiratory muscle strength. There was insufficient evidence for an effect on patient morbidity or health-related quality of life. iii) The pre-experimental, pilot study (n=8) suggested that a six-week inspiratory muscle training programme was safe, viable, acceptable and associated with a significant increase in inspiratory muscle strength. iv) The cross-over randomised controlled trial (n=23) did not show evidence of a difference in the primary outcome measures (number of hospitalisations and respiratory tract infections) between intervention and control periods. There were no adverse events related to inspiratory muscle training. Inspiratory muscle strength (Pimax) and peak expiratory cough flow increased by 14.57 (±15.67)cmH2O and 32.27 (±36.60)L/min respectively during the intervention period compared to a change of 3.04 (±11.93)cmH2O (p=0.01) and -16.59 (±48.29)L/min (p=0.0005) during the control period. There was no evidence of change in spirometry, functional ability or total health-related quality of life scores following the intervention. Overall participant satisfaction with inspiratory muscle training was high and adherence was good. Conclusions: Inspiratory muscle training in children with neuromuscular disease is well tolerated, appears to be safe and is associated with significant improvements in inspiratory muscle strength and cough efficacy.